Pharmacogenomics Implementation Training Improves Self-Efficacy and Competency to Drive Adoption in Clinical Practice - Adesta, Fadhli; Mahendra, Caroline; Junusmin, Kathleen Irena; Rajah, Arya Melissa Selva; Goh, Sharon; Sani, Levana; Chan, Alexandre; Irwanto, Astrid (Frontiers in Pharmacology, 2021)
Background: Administration of pharmacogenomics (PGx) testing in clinical practice has been suboptimal, presumably due to lack of PGx education. Here, we aim to evaluate the standpoint of PGx testing among a diverse group of healthcare professionals (HCPs) through conducting surveys before and after training. Materials & Methods: Training modules were designed to cover 3 key learning objectives and deployed in 5 sections. A pre- and post-training survey questionnaire was used to evaluate participants’ self-assessments on employing PGx in clinical practice. Results & Conclusion: Out of all enrollments, 102 survey responses were collected. Overall, respondents agree on the benefits of PGx testing, but have inadequate self-efficacy and competency in utilizing PGx data. Our results show that training significantly improves these, and could lead to greater anticipation of PGx adoption.